Pengaruh Variasi Arus Tabung (mA) Terhadap Kualitas Citra Pada Pesawat Computed Tomography (CT) Scan di RSUD Bali Mandara - I Dewa Ayu Sintiya Biantari; Gusti Ngurah Sutapa; Ida Bagus Alit Paramarta; I Nengah Sandi; Putu Suardana; Ni Komang Tri Suandayani; Hendra Setiawan (Universitas Hamzanwadi, 2025)
Computed Tomography (CT) Scan is one of the essential diagnostic tools in the medical field. CT scan image quality is represented by the Signal-to-Noise Ratio (SNR) and Contrast-to-Noise Ratio (CNR). This study was conducted to understand the effect of tube current variation on image quality in CT scan examinations. The CT scan parameters were set at an X-ray tube voltage of 120 kV, an exposure time of 1 second, and tube current variations of 100 mA, 200 mA, 300 mA, 400 mA, and 500 mA. From 25 image data obtained from scanning the Tos phantom on the CT scan, data were collected on the average signal intensity of the material, the average signal intensity of the background, and the standard deviation of the background signal intensity obtained from the Region of Interest (ROI) readings on each scanned phantom image. The Pearson correlation test results between tube current and SNR values showed that the Pearson correlation coefficient for polypropylene, nylon, acrylic, delrin, and air were 0.993, 0.992, 0.993, 0.992, and 0.992, respectively. The linear regression correlation coefficient (r) for polypropylene, nylon, acrylic, delrin, and air were also 0.993, 0.992, 0.993, 0.992, and 0.992, respectively. Similarly, the Pearson correlation test results between tube current and CNR values showed that the Pearson correlation coefficient for polypropylene, nylon, acrylic, delrin, and air were 0.992, 0.992, 0.993, 0.992, and 0.992, respectively. The linear regression correlation coefficient (r) for polypropylene, nylon, acrylic, delrin, and air were also 0.992, 0.992, 0.993, 0.992, and 0.992, respectively. These results indicate that for all phantom materials, the tube current value has a strong positive correlation with both SNR and CNR. The SNR and CNR values increase linearly with increasing tube current, suggesting that a higher tube current can improve CT scan image quality.